2019
DOI: 10.3390/v12010040
|View full text |Cite
|
Sign up to set email alerts
|

MYH9 Key Amino Acid Residues Identified by the Anti-Idiotypic Antibody to Porcine Reproductive and Respiratory Syndrome Virus Glycoprotein 5 Involve in the Virus Internalization by Porcine Alveolar Macrophages

Abstract: MYH9 has been identified as an indispensable cellular protein for porcine reproductive and respiratory syndrome virus (PRRSV) entry into permissive cells using the monoclonal anti-idiotypic antibody (Mab2-5G2) recognizing an antibody that specifically interacts with PRRSV glycoprotein 5 (GP5). More recently, we found that Mab2-5G2 interacted with the MYH9 C-terminal domain, designated PRA, which is required for PRRSV internalization. In this study, we demonstrate that blocking of MYH9 with Mab2-5G2 significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Diarrheal virus infection causes diarrhea, high mortality in piglets, and tremendous economic losses for swine farms worldwide. All swine enteric viruses—including TGEV, PEDV, PRV-A, and new variant strains PDCoV and SADS-CoV(Bevins et al 2018 ; Gong et al 2017 ; Pan et al 2017 ; Zhang et al 2015 ; Zhao et al 2019 )—could seriously endanger the development of the pig industry, especially in terms of newborn piglets. The symptoms caused by the above mentioned five viruses are similar, so it is difficult to determine the causative pathogen in clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Diarrheal virus infection causes diarrhea, high mortality in piglets, and tremendous economic losses for swine farms worldwide. All swine enteric viruses—including TGEV, PEDV, PRV-A, and new variant strains PDCoV and SADS-CoV(Bevins et al 2018 ; Gong et al 2017 ; Pan et al 2017 ; Zhang et al 2015 ; Zhao et al 2019 )—could seriously endanger the development of the pig industry, especially in terms of newborn piglets. The symptoms caused by the above mentioned five viruses are similar, so it is difficult to determine the causative pathogen in clinical diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that PRRSV entry is mediated by various cell receptors, such as sialoadhesin (Sn, CD169) [67,68], CD151 [69,70], heparin sulfate [71], vimentin [72], MYH9 [73,74], and CD163 (a scavenger receptor) [75]. Recently, CD163 was reported to be the key receptor during the process of PRRSV infection [76].…”
Section: Cd163 and Other Host Factors In Prrsv Infectionmentioning
confidence: 99%
“…The ectodomain of GP5 induces aggregation of MYH9 and facilitates viral internalization in both MARC-145 cells and PAMs [62]. Further studies showed that the amino acids E1670, K1673, E1679, and I1683 in the MYH9 C-terminal domain are the key binding residues, and a point mutation in E1670 in PAMs causes reduced permissiveness for PRRSV infection [63]. Overexpression of S100A4, which is an MYH9 disassembly inducer, downregulates the MYH9 aggregation and results in the inhibition of both PRRSV-1 and PRRSV-2 infection [62].…”
Section: Myh9mentioning
confidence: 99%